PENGARUH KONDISI PENCAHAYAAN TERHADAP HASIL SURVEI KECEPATAN KENDARAAN DENGAN PORTABLE SPEED GUN DAN APLIKASI BERBASIS ANDROID - Udi Subagyo Udi Subagyo; Achendri .Kurniawan (Universitas Islam Balitar Blitar, 2021)
Technological advances developed rapidly with the use of the Android system in 2007. Android is an operating system or mobile-based operating system that is very widely used today. Mainly on smart phones (smartphones) or tablets. In addition, Android has a large community of application developers that extend the functionality of the device, generally written in a customized version of the programming language. One of the applications based on android is the